2018
DOI: 10.1021/acsami.8b11300
|View full text |Cite
|
Sign up to set email alerts
|

High Thermoelectric Figure of Merit Achieved in Cu2S1–xTex Alloys Synthesized by Mechanical Alloying and Spark Plasma Sintering

Abstract: Chalcogenides have been considered as promising thermoelectric materials because of their low cost, nontoxicity, and environmental benignity. In this work, we synthesized a series of CuSTe (0 ≤ x ≤ 1) alloys by a facile, rapid method of mechanical alloying combined with spark plasma sintering process. The CuSTe system provides an excellent vision of the competition between pure phase and phase transformation, entropy-driven solid solution, and enthalpy-driven phase separation. When the Te concentration increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 65 publications
1
30
0
Order By: Relevance
“…However, deriving from simultaneously deteriorated carrier transport properties, the zT values cannot be effectively enhanced, as shown in Figure d. Similar influence of nanoengineering in Cu 2 S has also been found . Although nanoengineering can effectively reduce κ l of Cu 2 Se, high crystallinity is important for maintaining high electrical performance in nanoengineered Cu 2 Se and subsequently a high zT.…”
Section: Strategies For the Thermoelectric Property Enhancementmentioning
confidence: 69%
See 2 more Smart Citations
“…However, deriving from simultaneously deteriorated carrier transport properties, the zT values cannot be effectively enhanced, as shown in Figure d. Similar influence of nanoengineering in Cu 2 S has also been found . Although nanoengineering can effectively reduce κ l of Cu 2 Se, high crystallinity is important for maintaining high electrical performance in nanoengineered Cu 2 Se and subsequently a high zT.…”
Section: Strategies For the Thermoelectric Property Enhancementmentioning
confidence: 69%
“…[229][230][231][232] However, in Cu 2 X-based thermoelectric materials, some controversial phenomena have been observed. For example, heavy element doping on anion site can reduce κ l of Cu 2 Se, such as using I, [233] Te, [203,234] and S. [171] In contrast, Zhao et al [235] observed increased κ l after I and Te doping in Cu 2 Se. When the doping is on cation (Cu) site, for example, Guan et al [207] substituted Cu with Ag, inducing a large amount of CuAgSe secondary phase, which became solid-solution with the Cu 2 Se matrix when temperature was increased above 400 K, reduced the κ l .…”
Section: Point Defect Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 9 and 10). [8l,o, [26][27][28][29] When the solubility x is low, the low symmetry monoclinic crystal structure of the Cu 2−δ M matrix is well maintained at room temperature; when the solubility x is high, a high symmetry trigonal or hexagonal structure would form (cf. Figure 9).…”
Section: Cu 2−δ (S Se Te)-based Liquid-like Materialsmentioning
confidence: 99%
“…Mechanical alloying has, recently, been applied for industrializing a wide range of nanostructured materials through top down process and favor process for producing of intermetallic compounds such as Ni-Al, Ti-Al, Fe-Al, Nb-Al and pure metallic of Cr, Fe, Ti, Cu, Co, Nb as well as alloys of Ni-Si, Ni-Mo, Ni-Zr, Cu-Ta, Cu-W nanocrystals 136,137 . Fig.9 illustrates the Cu2-Te, Sm0.9 Mg0.1FeAsO0.8F0.2, p-type SnSe, Ti-B, Ti0.5V1.2Co0.3, Fe50Se50, TiFe and La-SrTiO3 nanocrystals were attended in this ways [138][139][140][141][142][143][144][145] . Using this technique, the oxide becomes dispersed along the boundaries of the alloy grains, resulting in an alloy with increased crawling strength compared to the same alloys without the oxide being dispersed in them 146 .…”
Section: Mechanical Alloying Processmentioning
confidence: 97%